(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
This paper seeks to understand the benefits of formative assessment, in contrast to summative assessment, which bases its method on results and not on processes, thus generating disinterest and demotivation in the learning process on the part of students. The objective is to explore and analyze the influence of formative assessment on student motivation, using a methodology based on literature review. The analysis examines a variety of sources, such as previous research and academic articles. The results reveal that formative assessment, by providing continuous feedback and guidance, plays a crucial role in fostering students’ intrinsic motivation. This feedback provides students with a clearer understanding of their progress, creating a sense of achievement and autonomy in their learning process. Through this literature review, it is confirmed that formative assessment contributes to creating a more stimulating and participatory educational environment, thus enhancing their learning process and motivation for learning.